CHARACTERISTICS OF POSSESSION OF THE BALL WHILE THE SENIOR AND PREPARATORY GROUPS OF PRESCHOOL INSTITUTIONS PERFORM THE ELEMENTS OF CHILDREN'S SOCCER (Conferencea, 2023)
The article analyzes the results of the observation of the performance of children’s football sport by senior and preparatory group students of pre-school institutions. The different characteristics of boys and girls are also compared with the provided results.